The effects of pore fluid on the undrained strength of kaolinite / by Charles C. Ladd, R. Torrence Martin. - Ladd, Charles C. (Charles Cushing); Martin, Robert T., author.; Massachusetts Institute of Technology. Soil Mechanics Division.; United States. Army Materiel Command.; U.S. Army Engineer Waterways Experiment Station. (Tufts University. Tisch Library., 2019)
1 online resource (55 leaves) : illustrations; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.